Just plain Wronga?: a multimodal critical analysis of online payday loan discourse - Brookes, Gavin; Harvey, Kevin (Taylor & Francis (Routledge), 2016)
Payday loans constitute one of the most rapidly expanding and controversial forms of consumer lending today. Payday lending – the selling of high-interest, short-term credit – has thrived in the wake of the decline of the traditional high street banking system and the reluctance on the part of many mainstream credit services, following the 2007/8 Global Financial Crisis, to lend to low income earners. This study critically examines the website of the industry leader in the UK, Wonga, a payday lender which recently rebranded and relaunched itself (in 2015) after being embroiled in a series of financial scandals. Our analysis centres on the new Wonga website, the gateway to its financial services, and identifies three inter-related discursive strategies through which the lender, in the wake of its financial misconduct, seeks to present itself as a reputable financial service provider, namely by (1) constructing the empowered and responsible borrower, (2) de-stigmatising both its service provision and its prospective customers, the payday borrower, and (3) minimising the consequences and risks associated with payday borrowing. We argue that, collectively, these strategies constitute an artful response by Wonga to the changing legislative and socio-economic contexts in which it and other payday lenders are now required to operate, permitting it to continue marketing and selling its high-interest rate financial services.